Androgen dysfunction in non-alcoholic fatty liver disease: Role of sex hormone binding globulin - Song, Myeong Jun; Choi, Jong Young (Frontiers in Endocrinology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is the most common form of chronic liver disease in the world. It is linked mainly to insulin resistance and metabolic syndrome including obesity and dyslipidemia. In addition, various endocrine dysfunctions including polycystic ovary syndrome (PCOS) and hypogonadism are involved in the development and progression of NAFLD. We need to know the disease pathophysiology more accurately due to the heterogeneity of clinical presentation of fatty liver disease. The liver is the major metabolic organ with sexual dimorphism. Sexual dimorphism is associated not only with behavioral differences between men and women, but also with physiological differences reflected in liver metabolism. In men, normal androgen levels prevent hepatic fat accumulation, whereas androgen deficiency induce hepatic steatosis. In women, higher androgens can increase the risk of NAFLD in PCOS. Sex hormone binding globulin (SHBG) is involved in androgen regulation. Recently, SHBG may be reported as a surrogate marker for NAFLD. Therefore, this review will focus on the mechanism of androgen dysfunction in the regulation of hepatic metabolism, the risk of developing NAFLD, and the potential role of SHBG in the course of NAFLD.